PANDEMI COVID-19 DAN BUDAYA KOMUNIKASI - Parapat, Nelson Halong (Istek Widuri Jakarta, 2021)
This paper aims to provide insightful knowledge to readers about the Covid-19 pandemic which causes changes in society related to habits or ways of communicating. It could be that the Covid-19 pandemic tends to create a new communication culture in society. The COVID-19 pandemic has forced employees to work from home (WFH). For students can study from home or distance learning. WFH, office meetings, seminars, and online learning or PJJ are carried out using online media, for example using Zoom Meetings and Google Meet. People are accustomed to using masks when doing speech communication and people are adapting to changes in vocal paralanguage that occur as a result of wearing masks. In addition, greetings or introductions change using namaste, which is a form of respect without physical contact and can be used universally when meeting other people of different gender, age, or social status. Namaste is said in front of other people, usually done respectfully with the palms of the hands together so that the palms and fingers touch each other, and placed in front of the chest while slightly lowering the head. This gesture can be done without words but it already contains the meaning conveyed by the greeting. In everyday life, the application of namaste can be equated with